2008
DOI: 10.1111/j.1751-908x.2008.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Determination by ICP‐AES and ICP‐MS: Developments and Applications Reported During 2006 and 2007

Abstract: GEOSTANDARDS andRESEARCH GEOANALYTICAL This review describes developments in trace element determination using inductively coupled plasma-atomic emission spectrometry (ICP-AES) and inductively coupled plasma-mass spectrometry (ICP-MS) that were reported in 2006 and 2007. It focuses on the application of ICP techniques to geological and environmental samples; fundamental studies in ICP-MS and ICP-AES instrumentation have largely been ignored. New advances in ICP-MS and ICP-AES were incremental over this period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 70 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…This is the fourth biennial review published in GGR of atomic absorption spectroscopy (AAS), instrumental neutron activation analysis (INAA), and X‐ray fluorescence (XRF) spectrometry (Bédard 2008). However, for the first time, inductively coupled plasma‐atomic emission spectrometry (ICP‐AES), previously covered in a separate review (Linge 2008), has also been included. In order to evaluate the activity of these analytical methods, a search was performed using the online bibliographic database ‘Web of Science’ using ‘atomic absorption’ and the abbreviations ‘INAA’, ‘XRF’ and ‘ICP‐AES’ or ‘ICP‐OES’, limited to analytical chemistry (Table 1).…”
Section: The Number Of Papers and Citations Reported By Web Of Sciementioning
confidence: 99%
“…This is the fourth biennial review published in GGR of atomic absorption spectroscopy (AAS), instrumental neutron activation analysis (INAA), and X‐ray fluorescence (XRF) spectrometry (Bédard 2008). However, for the first time, inductively coupled plasma‐atomic emission spectrometry (ICP‐AES), previously covered in a separate review (Linge 2008), has also been included. In order to evaluate the activity of these analytical methods, a search was performed using the online bibliographic database ‘Web of Science’ using ‘atomic absorption’ and the abbreviations ‘INAA’, ‘XRF’ and ‘ICP‐AES’ or ‘ICP‐OES’, limited to analytical chemistry (Table 1).…”
Section: The Number Of Papers and Citations Reported By Web Of Sciementioning
confidence: 99%
“…Despite the availability of advanced analytical instruments, such as atomic absorption spectroscopy (AAS) and inductively coupled plasma‐mass spectrometry (ICP‐MS), sample pretreatment is necessary for preconcentration and purification purposes during heavy metal analysis . It was previously reported that matrix interferences could affect the nebulizer performance; therefore, optimal instrumental modulation conditions are affected by sample purity . However, this problem can be minimized by the separation of the analyte from the matrix .…”
Section: Introductionmentioning
confidence: 99%
“…Determination of these elements requires sufficiently sensitive techniques for detection. In the literature, there are many techniques including flame atomic absorption spectrometry (FAAS) [8,11], electrothermal atomic absorption spectrometry (ETAAS) [12,13] inductively coupled plasma optical emission (ICP-OES) [14][15][16][17][18][19][20][21], mass spectrometry (ICP-MS) [22][23][24], X-ray and total reflection X-ray fluorescence techniques (TXRF), atomic fluorescence spectrometry (AFS), microwave-induced plasma source (MIP-OES and MIP-MS), laser-induced breakdown spectroscopy (LIBS), laserexcited atomic fluorescence spectrometry (LEAFS), and glow discharge mass spectrometry (GD-MS) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Modern environmental science maintains an interest in methods, which ensure the following important characteristics: (a) multielement analysis of a wide variety of environmental sample types; (b) it must be able to detect large number of elements at threshold concentration levels for a different type of samples. Among the modern instrumental methods for determination of trace elements, inductively coupled plasma optical emission spectrometry (ICP-OES) is very powerful [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation